(3dbWI GdaQGFO aj JMbjb GdahGFOs - (3CMeO Hf eMeO Hf eMeO Hf CHj GdYGajI GdecfGSj GdRfGJj, GdTgjQ HGHf GdbGVjs; (3GHf GdNWjH GdbSfWjfjs
(3ChdgG (B:s
(3hHYO , agPg hQjbGJ LeYJ ajgG ef cGf ef Chd GdeGFI GdKGefI Edi BNQ GdYGTQI s
(3BNQgG (B:s
(3hgj Chd LeYI NWHgG CHhYHOGddg GdePchQ HLGeY GdcJjHI hHYO GdMeO MV aj NWHJg Ydi WGYI GdSdWGf GfJgi eG hLO ceG hLO HMeO Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B136 - (3U(B184s
(3GfXQ Qbe (B427 (3JGQjNs
(3fSNI KGfjIs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B679 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B359 s
Keywords: (3GdJGQjNs